Real-Time Estimation of Traffic Self-Similarity Parameter in Simulink with Wavelet Transform - Grab, E.; Sarkovskis, S. (Elektronika ir Elektrotechnika, 2013)
The article describes P/M/1/K queuing model and Hurst parameter estimation unit with Wavelet Transform for real-time estimation of the traffic self-similarity parameter in Simulink. It consists of simulation results, which show the possibility to estimate Hurst parameter in real-time by means of Wavelet transform. It is offered to iteratively calculate the averaged Hurst parameter estimation, which improves the accuracy to the accuracy of the estimation over entire traffic series and in some cases even higher, as it has been shown in simulation results analysis. The estimation deviations have been analyzed as well as variance of such deviations. The results also give directions for further research to improve accuracy of traffic parameters estimation. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.3702